2021
DOI: 10.1021/acsomega.1c00020
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Dipeptide from Marine Fungus Penicillium chrysogenum DXY-1 Exhibits Anti-quorum Sensing Activity

Abstract: Bacterial quorum sensing (QS) is anticipated as a new potential target for the development of antimicrobial drugs. An anti-QS substance against Chromobacterium violaceum CV026 and Pseudomonas aeruginosa PA01 has been isolated and purified from the crude extracts of the marine fungus Penicillium chrysogenum DXY-1, and the accurate structure was identified as cyclo­(l-Tyr-l-Pro). This cyclic dipeptide at sub-minimum inhibitory concentration can decrease the QS-regulated violacein production of C. violaceum CV026… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Additionally, Kumar et al reported the isolation of proline-containing DKPs, namely cyclo(D-Pro-L-Leu), cyclo(L-Pro-L-Met), cyclo(L-Pro-L-Phe), cyclo(D-Pro-L-Phe), cyclo(D-Phe-L-Pro), cyclo(D-Pro-D-Phe) and cyclo(L-Pro-D-Phe) isomers, as well as cyclo(L-Pro-L-Tyr), and cyclo(L-Pro-D-Tyr) from a culture filtrate of a Bacillus bacterial strain associated with an entomopathogenic nematode. These cyclic dipeptides showed significantly higher activity than the commercial fungicide bavistin against Fusarium oxysporum, Rhizoctonia solani, and Pencillium expansum [227,236,237]. Cyclo(L-Pro-L-Leu), cyclo(D-Pro-L-Leu), and cyclo(D-Pro-L-Tyr) displayed superior antifungal activity against Aspergillus flavus, Candida albicans, and F. oxysporum [41].…”
Section: Antifungal Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, Kumar et al reported the isolation of proline-containing DKPs, namely cyclo(D-Pro-L-Leu), cyclo(L-Pro-L-Met), cyclo(L-Pro-L-Phe), cyclo(D-Pro-L-Phe), cyclo(D-Phe-L-Pro), cyclo(D-Pro-D-Phe) and cyclo(L-Pro-D-Phe) isomers, as well as cyclo(L-Pro-L-Tyr), and cyclo(L-Pro-D-Tyr) from a culture filtrate of a Bacillus bacterial strain associated with an entomopathogenic nematode. These cyclic dipeptides showed significantly higher activity than the commercial fungicide bavistin against Fusarium oxysporum, Rhizoctonia solani, and Pencillium expansum [227,236,237]. Cyclo(L-Pro-L-Leu), cyclo(D-Pro-L-Leu), and cyclo(D-Pro-L-Tyr) displayed superior antifungal activity against Aspergillus flavus, Candida albicans, and F. oxysporum [41].…”
Section: Antifungal Activitymentioning
confidence: 94%
“…In another study, cyclo(L-Phe-L-Pro) produced by Vibrio vulnificus was found to activate the quorum sensing on an E. coli biosensor strain by modulating the expression of the gene encoding OmpU protein [231]. Finally, cyclo(L-Phe-L-Pro) and cyclo(L-Pro-L-Tyr) produced by Lactobacillus reuteri, were reported to interfere with quorum sensing in the Gram-positive S. Aureus [41,221,227,[232][233][234].…”
Section: Quorum-sensing Agonists and Antagonistsmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies have shown that the expression of virulence factors for pathogenicity in P. aeruginosa is regulated by its QS system [14,15]. In the past few years, several known compounds, including some cyclic dipeptides, proved to exhibit anti-QS activity, such as chrysin, tyrosol, cyclo (L-Tyr-L-Pro) from Penicillium chrysogenum [16][17][18], cyclo (L-Trp-L-Ser) from Rheinheimera aquimaris [19], and cyclo (L-Phe-L-Pro) from Sphingomonas sp. WG [20].…”
Section: Introductionmentioning
confidence: 99%
“…CDPs are indeed attracting interest as drug carriers, thanks to their demonstrated ability to cross membranes and penetrate cells [ 29 ]. Their aggregates can display fluorescence [ 30 ], and they are widely studied for their diverse biological activities [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], which make them promising for biomedical applications, as recently reviewed [ 39 ]. Further, they are being investigated also for optoelectronic [ 40 ] and catalytic [ 41 ] applications, as biodegradable and environmentally-friendly substitutes of more traditional options.…”
Section: Introductionmentioning
confidence: 99%